Structural investigations into the binding mode of novel neolignans Cmp10 and Cmp19 microtubule stabilizers by in silico molecular docking, molecular dynamics, and binding free energy calculations. Issue 6 (2nd June 2016) - Tripathi, Shubhandra; Kumar, Akhil; Kumar, B. Sathish; Negi, Arvind S.; Sharma, Ashok
Abstract : Microtubule stabilizers provide an important mode of treatment via mitotic cell arrest of cancer cells. Recently, we reported two novel neolignans derivatives Cmp10 and Cmp19 showing anticancer activity and working as microtubule stabilizers at micromolar concentrations. In this study, we have explored the binding site, mode of binding, and stabilization by two novel microtubule stabilizers Cmp10 and Cmp19 using in silico molecular docking, molecular dynamics (MD) simulation, and binding free energy calculations. Molecular docking studies were performed to explore the β-tubulin binding site of Cmp10 and Cmp19 . Further, MD simulations were used to probe the β-tubulin stabilization mechanism by Cmp10 and Cmp19 . Binding affinity was also compared for Cmp10 and Cmp19 using binding free energy calculations. Our docking results revealed that both the compounds bind at Ptxl binding site in β-tubulin. MD simulation studies showed that Cmp10 and Cmp19 binding stabilizes M-loop (Phe272-Val288) residues of β-tubulin and prevent its dynamics, leading to a better packing between α and β subunits from adjacent tubulin dimers. In addition, His229, Ser280 and Gln281, and Arg278, Thr276, and Ser232 were found to be the key amino acid residues forming H-bonds with Cmp10 and Cmp19, respectively. Consequently, binding free energy calculations indicated that Cmp10 (−113.655 kJ/mol) had better binding compared to Cmp19 (−95.216 kJ/mol). This study provides useful insight for better understanding of the binding mechanism of Cmp10 and Cmp19 and will be helpful in designing novel microtubule stabilizers.